Capital Market Reaction to the 2024 General Election (Case Study of LQ45 Shares on the Indonesia Stock Exchange) - Jaya, Fauziah Nur Khasanah Tri; Lestari, Wuryaningsih Dwi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study utilizes an event study approach to examine stock market responses to Indonesia's 2024 General Election. The focus is to evaluate market reactions among companies listed in the LQ45 index, analyzing stock performance both before and after the election. Methodology: This quantitative research relies on secondary data, selecting 26 stocks from companies in the LQ45 index through purposive sampling. The study applies the event study technique over a 126-day period, comprising 115 days for estimation and an 11day event window. This event window is split into three segments: five days before the event (t-5), the day of the event (t0), and five days after the event (t+5). Results: Findings from the abnormal return (AR) statistical test conducted around the election period show a significant negative effect on day T+1 after the election on stock market performance. Moreover, a noticeable difference in average abnormal return (AAR) was identified before and after the election, suggesting that the event provides investors with new, divergent information. Applications/Originality/Value: This research underscores that general elections can significantly impact stock market behavior. Accordingly, investors are advised to consider risk mitigation strategies when investing in the stock market during election periods.